2021
DOI: 10.5937/jemc2102124z
|View full text |Cite
|
Sign up to set email alerts
|

Modern technologies influence on project success factors in IT sector of Serbia

Abstract: Given the technological advances and the recognized importance of the application of technologies in project management, the question arises whether the technologies of Industry 4.0 can solve the problem of failure of information technologies (IT) projects. This question is the main motivator for writing this paper and conducting research on this topic. This paper describes a research that was conducted with the intention of examining the extent to which modern technologies can contribute to the success of IT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…Consequently, the hypothesis was rejected, leading to the conclusion that there exists a significant relationship between technological factors and the performance of road construction projects in Nairobi County, Kenya. This result is consistent with research byZorić et al (2021) that examined the role that contemporary technology has in the accomplishment of IT projects. The study demonstrated how contemporary technologies are being used in Serbia's IT industry for project management, and it highlighted the benefits of technological incentives for project success by examining how they affect different success criteria.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Consequently, the hypothesis was rejected, leading to the conclusion that there exists a significant relationship between technological factors and the performance of road construction projects in Nairobi County, Kenya. This result is consistent with research byZorić et al (2021) that examined the role that contemporary technology has in the accomplishment of IT projects. The study demonstrated how contemporary technologies are being used in Serbia's IT industry for project management, and it highlighted the benefits of technological incentives for project success by examining how they affect different success criteria.…”
supporting
confidence: 90%
“…It is noteworthy that while the study concentrated on the construction industry, it did not specifically address roads construction projects. Zorić et al (2021) explored the contribution of modern technologies to the success of IT projects. Employing a Quantitative Mono Method, the research examined the application of modern technologies in project management within the IT sector of Serbia.…”
Section: Empirical Reviewmentioning
confidence: 99%